Sheep in the tropics: an undervalued resource - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Sheep, like other domesticated ruminant species, have adapted to a wide range of environments from the temperate regions through to the humid tropics, including some of the world's most arid areas. Unlike the commercial production systems - both...